Exploring an alternative access route to higher education in South Africa: A human development and social justice analysis - Mkwananzi, Faith; Martinez Vargas, Carmen (Critical Studies in Teaching and Learning, 2024)
Widening access to higher education is one of the key policy priorities for many countries and institutions globally. While the concern has been to increase the number of young people entering university, there has also been interest in the diversity of people entering university, such as women, working students, and those from rural communities. This paper builds on that body of knowledge by combining ideas from the capability approach and social justice to understand what widening access may mean through a human development lens in contexts of historical injustice and inequality. It draws on the University Preparation Programme (UPP) and the Extended Programme (EP) provided by one of the universities in South Africa as a route to expand access and participation for students who might otherwise not access university. In doing so, it presents empirical and theoretical contributions to the multidimensionality of inequalities and how these influence higher education opportunities.